Design and fabrication of plastic waste crusher / Muhammad Amsyar Faheem M. Suaree - M. Suaree, Muhammad Amsyar Faheem (2023)
This project aims to develop a plastic waste crusher that could help in crashing plastics. The crusher could crush several items such as plastic bottles where the main material for this object is plastic. A plastic waste crusher is a machine that helps in crushing plastic waste manually. People usually have a problem crushing their own plastic waste because they think that it causes a lot of inconvenience where one needs to crush it by themselves, and it needs a lot of energy to crush it. The method of making this machine is using a lot of machining processes such as joining and welding to produce a good and strong product. Any plastic waste can be put into this machine and the machine can help to crush the plastic into tiny pieces. It is more cost-effective when people crush their own plastic waste before throwing it out. Even though it may seem not important, everyone must know that there are many advantages to crushing the plastic waste before throwing it away. Other than that, this machine can also help small industries to crush their plastic waste and help to reduce the volume of plastic waste. In conclusion, this product will bring such a huge effect to the community and environment where it will make it easier for humans to crush the plastic waste and save the environment from plastic waste pollution